Love, Loss, and Resilience: an in-depth Literary Analysis of 'All the Bright Places' (2015) through the Lens of Existentialism - Titis Setyabudi; Basyir Yasier Rais (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This in-depth literary analysis explores the novel "All the Bright Places" (2015) by Jennifer Niven This research examines an existentialist perspective, focusing on the themes of love, loss, and resilience. By applying an existentialist lens with the aim of (1) From an existentialist perspective, how the themes of love, loss, and resilience are expressed in this novel; (2) Analyze the concepts of individual freedom and personal responsibility in this novel and the existentialist implications that arise from the characters and storyline; (3) Discover the role of the themes of death and loss in this story and how they can be understood through the lens of existentialism. This research method is a descriptive qualitative method using content analysis techniques and note-taking techniques in data analysis. The data of this research comes from the literary work All the Bright Places (2015). Through this exploration, this research reveals the timeless exploration of humanity and existentialism in literature